2021
DOI: 10.1021/acsami.0c17549
|View full text |Cite
|
Sign up to set email alerts
|

On the Correlation between Light-Induced Degradation and Minority Carrier Traps in Boron-Doped Czochralski Silicon

Abstract: Boron-doped Czochralski grown silicon wafers dominate the photovoltaic market. Light-induced degradation of these wafers is one of the most significant roadblocks for high-efficiency solar cells. Despite a very large number of publications on this topic, only a few studies have directly investigated the precursor of the defect responsible for this degradation. In this study, using the photoconductance decay measurement method, we identify the precursor of the defect responsible for light-induced degradation. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…[14,15] In Cz-Si:B, this defect has been argued to be the precursor of the light-induced degradation (LID) defect, which is responsible for the reduction in the lifetime and efficiency of the silicon solar cells. [14,16,17] It can be observed that the boron-doped Cz-Si and indiumdoped samples (In-3) with almost similar doping concentrations of about (4.0-4.5) Â 10 15 cm À3 have a similar trap concentration in the range of (3.0-3.5) Â 10 13 cm À3 . It should be noted that the trap concentration values are derived using the equation:…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[14,15] In Cz-Si:B, this defect has been argued to be the precursor of the light-induced degradation (LID) defect, which is responsible for the reduction in the lifetime and efficiency of the silicon solar cells. [14,16,17] It can be observed that the boron-doped Cz-Si and indiumdoped samples (In-3) with almost similar doping concentrations of about (4.0-4.5) Â 10 15 cm À3 have a similar trap concentration in the range of (3.0-3.5) Â 10 13 cm À3 . It should be noted that the trap concentration values are derived using the equation:…”
Section: Resultsmentioning
confidence: 99%
“…During prolonged injection of minority carriers, the B s O 2 complex transforms to a configuration with a shallow acceptor level and enhanced recombination activity. [ 14,16,17 ] This transformation results in a reduction of the minority carrier lifetime in boron‐doped Cz‐Si; i.e., it causes the BO LID of silicon solar cells. [ 14,16,17 ]…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations